Early Phase Increase in Serum TIMP-1 in Patients with Acute Encephalopathy with Biphasic Seizures and Late Reduced Diffusion - Ayaka Kasai; Jun Kobayashi; Makoto Nishioka; Noriko Kubota; Yuji Inaba; Mitsuo Motobayashi (MDPI AG, 2022)
Background: Acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) is the most frequent subtype of acute encephalopathy syndrome among Japanese children. Exanthem subitum is the most common causative infectious disease of AESD. We herein retrospectively analyzed serum and cerebrospinal fluid (CSF) concentrations of matrix metalloproteinase-9 (MMP-9), tissue inhibitor matrix metalloproteinase-1 (TIMP-1), and seven cytokines in patients with AESD or prolonged febrile seizure (FS) to assess the pathophysiology of AESD and detect biomarkers for diagnosing AESD in the early phase. Methods: Serum and CSF samples were obtained from 17 patients with AESD (1st seizure phase group, n = 7; 2nd seizure phase group, n = 10) and 8 with FS. The concentrations of MMP-9, TIMP-1, and seven cytokines were measured by enzyme-linked immunosorbent assays or cytometric bead arrays. Results: Serum concentrations of TIMP-1 were significantly higher in the 1st seizure phase group than in the 2nd seizure phase group. No significant differences were observed in serum concentrations of MMP-9 or the MMP-9/TIMP-1 ratio. Conclusions: The MMP-9-independent increase in circulating TIMP-1 concentrations observed in the present study may be associated with the pathophysiology of AESD in the 1st seizure phase.